THIN FILMS OF BINARY CHALKOGENIDES As2X3 (X = S, Se) PREPARED BY SPIN COATING METHOD - H. N. Thi; E. V. Tekshina; P. I. Lazarenko; V. K. Ivanov; S. A. Kozyukhin (Российский технологический журнал)
This paper describes the processes of preparing solutions of binary vitreous semiconductor materials As2X3 (X = S, Se) and fabricating thin films based on them by spin coating. The initial materials are synthesized using semiconductor purity grade solvents by the direct synthesis in pre-vacuumed quartz vials at a maximum temperature of 750ºС and identified by the authors as glass. The obtained amorphous thin films are proven to have an island morphology. The thickness of the As2S3 film can vary in the range of 200 nm (at an average roughness of 0.7 nm) to 2.5 μm (at an average roughness of 100 nm). The thickness of the As2Se3 film can vary in the range of 200 nm (at an average roughness of 8 nm) to 3 μm (at an average roughness of 200 nm). The optical characteristics of thin films are also studied, in particular optical transmission in the visible spectrum. The band gap of the obtained films is determined by employing a Tauc plot. The findings of the experiment are compared with the literature data.